Low Genetic Diversity and Structuring of the Arapaima (Osteoglossiformes, Arapaimidae) Population of the Araguaia-Tocantins Basin - Vitorino, Carla A.; Nogueira, Fabrícia; Souza, Issakar L.; Araripe, Juliana; Venere, Paulo C. (Frontiers in Genetics, 2017)
The arapaima, Arapaima gigas, is a fish whose populations are threatened by both overfishing and the ongoing destruction of its natural habitats. In the Amazon basin, varying levels of population structure have been found in A. gigas, although no data are available on the genetic diversity or structure of the populations found in the Araguaia-Tocantins basin, which has a topographic profile, hydrological regime, and history of fishing quite distinct from those of the Amazon. In this context, microsatellite markers were used to assess the genetic diversity and connectivity of five wild A. gigas populations in the Araguaia-Tocantins basin. The results of the analysis indicated low levels of genetic diversity in comparison with other A. gigas populations, studied in the Amazon basin. The AMOVA revealed that the Arapaima populations of the Araguaia-Tocantins basin are structured significantly. No correlation was found between pairwise FST values and the geographical distance among populations. The low level of genetic variability and the evidence of restricted gene flow may both be accounted for by overfishing, as well as the other human impacts that these populations have been exposed to over the years. The genetic fragility of these populations demands attention, given that future environmental changes (natural or otherwise) may further reduce these indices and eventually endanger these populations. The results of this study emphasize the need to take the genetic differences among the study populations into account when planning management measures and conservation strategies for the arapaima stocks of the Araguaia-Tocantins basin.